Adherence of Bordetella bronchiseptica 276 to porcine trachea maintained in organ culture. - Dugal, F (1990)
Two organ culture models have been adapted for porcine tracheae in order to study colonization by Bordetella bronchiseptica. Rings or segments excised from tracheae of newborn piglets were incubated overnight at 37 degrees C in a nutrient medium under 5% CO2-95% air conditions. Tracheal segments were infected with B bronchiseptica 276, and after different incubation times, bacterial counts were done. B. bronchiseptica adhered well to tracheae maintained in culture, and no statistically significant differences between the two models were observed. Noninfected tracheal mucosae maintained a normal appearance for several days, whereas infected mucosae showed typical damage caused by B. bronchiseptica, namely, loss of ciliary activity and cilia and sloughing of ciliated cells. Our data indicated that porcine tracheal organ culture could be advantageously used to study in vitro colonization by B. bronchiseptica.